The relationship of lower-body, multijoint, isometric and dynamic neuromuscular assessment variables with snatch, and clean and jerk performance in competitive weightlifters: A meta-analysis - Joffe, S. A.; Price, P.; Chavda, S.; Shaw, J.; Tallent, J. (Strength and Conditioning Journal, 2023)
The purpose of this meta-analysis was to synthesize the literature and provide a robust estimate of the correlations between lower-body, multijoint, isometric and dynamic neuromuscular assessment variables and snatch (SN) and clean and jerk (C&J) performance in competitive weightlifters. A comprehensive search through 3 electronic databases (PubMed, SPORTDiscus, and Web of Science) returned 12 studies that met the inclusion criteria. Meta-analyses were performed on Pearson's correlations between SN and C&J performance and 15 variables from 5 neuromuscular assessments—countermovement jump (CMJ), squat jump (SJ), isometric midthigh pull (IMTP), back squat (BS), and front squat (FS) one repetition maximum (1RM). The FS and BS 1RM exhibited nearly perfect correlations (r = 0.93 to 0.94), whereas the IMTP peak force exhibited very large correlations (r = 0.83 to 0.85). The IMTP force at 250 ms exhibited very large correlations (r = 0.77 to 0.78), and the CMJ and SJ peak power exhibited very large to nearly perfect correlations (r = 0.88 to 0.92). These findings illustrate the importance of lower-body maximal and time-limited force-producing capabilities in weightlifters. Moreover, each assessment offers at least one variable that exhibits a correlation of >0.70. Therefore, these assessments may be used to gauge weightlifting performance potential.